165k views
3 votes
Help please please please please

Help please please please please-example-1
User Radzio
by
5.5k points

2 Answers

3 votes

Answer:

y-6=-6(x-1)

Explanation:

Hope this helps :D

have a nice thanksgiving

User Kimmeh
by
5.5k points
1 vote

Answer:


y-6=-6(x-1)

Explanation:

A point-slope equation requires two values in order to write it: one coordinate and the slope.

First, find the slope between the two given points. To find the slope, you would subtract the first Y from the second Y and the first X from the second X. Y goes on top of the fraction bar, making the equation look like this:


(6-(-6))/(1-3)

Then, simplify the slope equation:


(6-(-6))/(1-3) = (6+6)/(1-3) = (12)/(-2) = -6

The slope is -6.

Finally, choose one of the coordinates. For this, I'll pick (1, 6).

The point-slope equation is
y-y_(1) =m(x-x_(1))

So, simply fill in the
m,
y_(1) , and
x_(1) spots with the value we have found.


m is the slope, so replace it with -6.


y_(1) = 6


x_(1) = 1

Final answer:


y-6=-6(x-1)

User Sequoyah
by
5.8k points